2006
DOI: 10.1121/1.2221415
|View full text |Cite
|
Sign up to set email alerts
|

Temporal integration of the contralateral acoustic-reflex threshold and its age-related changes

Abstract: Although numerous studies have investigated temporal integration of the acoustic-reflex threshold (ART), research is lacking on the effect of age on temporal integration of the ART. Therefore the effect of age on temporal integration of the ART was investigated for a broad-band noise (BBN) activator. Subjects consisted of two groups of adults with normal-hearing sensitivity: one group of 20 young adults (ten males and ten females, ages 18-29 years, with a mean age of 24 years) and one group of 20 older adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…However, the N1m and P2m latencies were both longer in older adults. These age-related increases are consistent with prior research (Matilainen et al, 2010;Tremblay et al, 2002) and may reflect a slowing in auditory processing and/or a broadening of the temporal integration window (Emmer et al, 2006;Gleich et al, 2007;Huang et al, 2009), with older adults reaching a saturation in the auditory evoked responses at a longer latency than young adults. An agerelated decline in temporal integration could also account for the reduced ORNm amplitude observed in our prior study (Alain and McDonald, 2007).…”
Section: Effects Of Age and Noise On The Speed Of Auditory Processingsupporting
confidence: 86%
“…However, the N1m and P2m latencies were both longer in older adults. These age-related increases are consistent with prior research (Matilainen et al, 2010;Tremblay et al, 2002) and may reflect a slowing in auditory processing and/or a broadening of the temporal integration window (Emmer et al, 2006;Gleich et al, 2007;Huang et al, 2009), with older adults reaching a saturation in the auditory evoked responses at a longer latency than young adults. An agerelated decline in temporal integration could also account for the reduced ORNm amplitude observed in our prior study (Alain and McDonald, 2007).…”
Section: Effects Of Age and Noise On The Speed Of Auditory Processingsupporting
confidence: 86%
“…In a prior study using the same stimuli and listening conditions (Alain et al, 2012), we found age-related increases in N1m and P2m latencies, which was consistent with earlier research (e.g.,Tremblay et al, 2002; Matilainen et al, 2010). The age-related increase in latency of auditory evoked responses may reflect a slowing in auditory processing and/or a broadening of the temporal integration window (Emmer et al, 2006; Gleich et al, 2007; Huang et al, 2009) with older adults reaching a saturation in the auditory evoked responses at a longer latency than young adults. The fact that the ORN latency was comparable between older adults with and without hearing loss suggests that mild hearing loss does not significantly delay the early computation needed to segregate the mistuned harmonic as a separate sound object.…”
Section: Discussionmentioning
confidence: 99%
“…The activating stimulus was a 1000 Hz signal with the same durations used for the BBN activator by Emmer et al (2006), that is, 12, 25, 50, 100, 200, 300, 500, and 1000 msec. A 1000 Hz stimulus was chosen because this frequency seems to be unaffected by adaptation regardless of age.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was the same as that reported by Emmer et al (2006). One ear of each subject in each group was randomly selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation